Coplanar waveguide low pass filter based on square complementary split ring resonator with wide rejection - Mohammed Bendaoued; Rachid Mandry; Larbi El Abdellaoui; Aytouna Fouad; Mohamed Latrach; Ahmed Lakhssassi (Universitas Ahmad Dahlan, 2020)
In this paper, we present a novel coplanar waveguide low pass filter (LPF)structure based on the use of square complementary split ring resonators (CSRRs) in order to enhance the performances of a low pass filter. Especially, to enlarge the bandwidth of the LPF, the insertion losses and to increase the rejection of the LPF. The CSRRs are optimised and inserted periodically along the center conductor of the CPW line with a CPW ground integrating stubs permitting to enlarge the bandwidth. The simulation results of this filter show a -3 dB cut-off frequency equal to fc = 5.28 GHz. The designed filter has a good rejection in the stop band which below -20 dB and presents a good insertion loss in the bandwidth. The proposed filter has been fabricated and tested which give a good agreement between simulation and measurement results, the whole dimensions of the validated filter are 35.48x21.16 mm2. The originality of this work is the wide rejection band and the miniature dimensions.